Choice-set forms are dual to outcome-set forms - Peter A. Streufert (The University of Western Ontario, Department of Economics, 2015)
Alós-Ferrer and Ritzberger (2013) specify each node in a game tree as the set of outcomes that yet remain conceivable. In contrast, Streufert (2015a) specifies each node as the set of choices that have already been made. This symmetry suggests that the two formulations are "dual" in some sense. In this paper I develop this duality. In particular, I define suit- able conversion procedures, and show that there is a one-to-one correspondence between choice-set forms and outcome-set forms. The analysis encompasses discrete forms with finite or infinite horizons.
Keywords: 330